2017
DOI: 10.1590/s0004-2803.201700000-51
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab for Ulcerative Colitis: Results of a Brazilian Multicenter Observational Study

Abstract: -Background -Adalimumab is a monoclonal antibody, tumor necrosis factor-alpha (TNFα) inhibitor that has efficacy for inducing and maintaining remission in moderate-to-severe ulcerative colitis. Real world studies with adalimumab in Latin American ulcerative colitis patients are scarce.Objective -To assess the clinical remission rates in induction and maintenance with adalimumab therapy in ulcerative colitis. Declared conflict of interest of all authors: Damião AOMC (Nestle, Janssen, Abbvie, Pfizer and Takeda),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
4
0
2
Order By: Relevance
“…The results of the present study are in tune with the reported efficacy of these agents in the real-world scenario, where the proportion of responders after 52 weeks of exposure varies from 30 to 65% for ADA [ 7 10 , 13 , 17 , 18 ] and from 39 to 70% for IFX [ 11 , 19 22 ], respectively. The discrepancy in the performance of biologics between the real-world scenario and pivotal studies is usually attributable to the restriction of concomitant treatments that could favor a response and the required washout period between one drug and another in the design of randomized clinical trials.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of the present study are in tune with the reported efficacy of these agents in the real-world scenario, where the proportion of responders after 52 weeks of exposure varies from 30 to 65% for ADA [ 7 10 , 13 , 17 , 18 ] and from 39 to 70% for IFX [ 11 , 19 22 ], respectively. The discrepancy in the performance of biologics between the real-world scenario and pivotal studies is usually attributable to the restriction of concomitant treatments that could favor a response and the required washout period between one drug and another in the design of randomized clinical trials.…”
Section: Discussionsupporting
confidence: 83%
“…In this scenario, there is lack of data on the efficacy and safety of anti-TNF agents in Brazilian patients in UC, as public and private access to these agents is relatively recent [ 13 ]. Therefore, the present study aimed to analyze rates of clinical and endoscopic remission comparatively, between ADA and IFX, in Brazilian UC patients, and evaluate possible factors associated with clinical and endoscopic remission after 1 year of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few published observational cohort studies in UC setting with patients having been treated with adalimumab [21][22][23]. However, these hitherto studies report short-term treatment outcomes (within 12 months), and we could not find any study on adalimumab treatment having a 6-year follow up.…”
Section: Discussionmentioning
confidence: 81%
“…There are descriptions of the efficacy and safety of anti-TNF agents in Latin America (14)(15)(16) . However, to date, there is scarce data on the precise penetration and frequency of use of biological agents in the management of IBD in our continent.…”
Section: Introductionmentioning
confidence: 99%